Sharia Law Implementation in Aceh: Exploring Feminization of Poverty and Local Policy Effect - Darwin, Rizkika Lhena; Fajarni, Suci; Safri, T. Mulkan (Journal of Administration, Governance, and Political Issues, 2025)
Many studies on poverty have been conducted using a development approach, which has evolved to include typologies of poverty (structural and cultural poverty), factors causing poverty, and government policies to combat it. One of the current focuses is the feminization of poverty, given that women are a large social entity but are structurally vulnerable. This article explores the relationship between local government policies and women's poverty, particularly the implementation of Islamic Sharia law in Aceh as a local policy. While Sharia policies are nominally intended to provide protection and security for women, in practice, these policies have not been fully gender-responsive. Research findings indicate that poor women in Aceh face double pressures due to economic poverty and social restrictions based on conservative interpretations of Sharia law and a strong patriarchal culture. Through a qualitative approach and feminist political economy analysis, this article concludes that local policies that do not integrate a gender perspective actually exacerbate the feminization of poverty. Therefore, participatory and inclusive Islamic gender justice-based policies are needed to create effective protection and empowerment for poor women in Aceh.